PELAKSANAAN TUGAS DAN TANGGUNG JAWAB ROOM ATTENDANT DI HOTEL GRAND ANTARES INDONESIA - Sianipar, Tetty Elprida; ', Etika (Fakultas Ilmu Sosial dan Ilmu Politik Universitas Riau, 2025)
This study aims to analyze the implementation of the duties and responsibilities of room attendants at Hotel Grand Antares Indonesia, as well as to identify the operational challenges that arise As one of the four-star hotels in Medan, Hotel Grand Antares is required to maintain the quality of service to meet the needs of both leisure and business guests. This research uses a descriptive qualitative approach with data collection techniques such as in-depth interviews, direct observation, and documentation. The findings indicate that the duties of room attendants include room inspections, providing guest amenities, reporting lost and found items, and maintaining cleanliness in the areas according to the established standard operating procedures (SOP). However, challenges such as time constraints, limited workforce, and lack of coordination between departments often hinder the achievement of optimal work efficiency. This study concludes that the implementation of the duties and responsibilities of room attendants at Hotel Grand Antares Indonesia meets most of the established service standards. However, improvements in time management, regular training, and enhanced interdepartmental coordination are necessary to increase operational efficiency and the overall guest experience Keywords: Implementation of room attendant duties, operational challenges, SOP